2020
DOI: 10.1038/s41598-020-75922-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive neuromodulation effects on painful diabetic peripheral neuropathy: a systematic review and meta-analysis

Abstract: Diabetic Peripheral Neuropathy (DPN) typically is accompanied by painful symptoms. Several therapeutic agents have been tried for symptomatic relief, but with varying results. The use of non-invasive neuromodulation (NINM) is a potential treatment option for DPN. The objective of our study is to evaluate NINM effects on pain rating and nerve conduction velocity in DPN patients. The search was carried out in seven databases until Aug 30th, 2019. Finally, twenty studies met the inclusion criteria. We found a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
(88 reference statements)
0
8
0
1
Order By: Relevance
“…There were five reviews on painful peripheral diabetic neuropathy ( Table 13 ). The most recent review published Zeng et al [ 169 ] was published in 2020 and included seven studies and a meta-analysis on that pooled data from various peripheral electrical stimulation techniques that failed to find differences with controls. However, the authors claimed that their subgroup analysis demonstrated “… a large effect for one of its subgroups (electrical peripheral techniques, predominantly TENS) …”, although the effect size for TENS per se was not reported and pooled samples did not reach our threshold for sufficient data to make a judgement.…”
Section: Resultsmentioning
confidence: 99%
“…There were five reviews on painful peripheral diabetic neuropathy ( Table 13 ). The most recent review published Zeng et al [ 169 ] was published in 2020 and included seven studies and a meta-analysis on that pooled data from various peripheral electrical stimulation techniques that failed to find differences with controls. However, the authors claimed that their subgroup analysis demonstrated “… a large effect for one of its subgroups (electrical peripheral techniques, predominantly TENS) …”, although the effect size for TENS per se was not reported and pooled samples did not reach our threshold for sufficient data to make a judgement.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the synthesis results for the low frequencies (1 and 0.5 Hz) showed no difference or were mixed, meaning these intervention protocols may be less effective or inappropriate for some specific NPs. (3) The impact of the quality Galhardoni et al, 2015;Jin et al, 2015;Kumru et al, 2017;O'Connell et al, 2018*;Aamir et al, 2020;Liampas et al, 2020b;Moisset et al, 2020b;Yang and Chang, 2020;Zeng et al, 2020Onesti et al, 2013 Cragg et al, 2016;Gao et al, 2017;O'Connell et al, 2018*;Akyuz and Giray, 2019;Nardone et al, 2019;Aamir et al, 2020;Gatzinsky et al, 2020;Moisset et al, 2020b;Shen et al, 2020;Chang, 2020 Yilmaz et al, 2014*;Ma et al, 2015;Malavera et al, 2016;Choi and Chang, 2018 Lin et al, Kumar et al, 2009;Leung et al, 2009;Zaghi et al, 2011;Galhardoni et al, 2015;Chen et al, 2016;Gao et al, 2017;Kumru et al, 2017;Herrero Babiloni et al, 2018;O'Connell et al, 2018*;Gatzinsky et al, 2020;Moisset et al, 2020a;Yang and Chang, 2020Lefaucheur et al, 2004…”
Section: Discussion Principal Findings Of Evidence Mappingmentioning
confidence: 99%
“…Qualitative studies may arrive at conclusions different from those in quantitative studies. For example, a primary study by Onesti et al (2013) and meta-analysis of Zeng et al (2020) had a “no difference” conclusion, while the review of Yang and Chang (2020) , which only mentioned pain relief, showed a “potentially better” conclusion. The final conclusion in the evidence map of Onesti et al’s study was “mixed.” (3) Populations with different diseases that cause NP could cause heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A neuromodulação não invasiva em pacientes com sintomas de resistência ou intolerância a medicamentos analgésicos podem ser alternativas seguras, mas são necessárias mais evidências antes que as recomendações de tratamento possam ser feitas. (Zeng et al, 2020). Terapias eletrofísicas como terapia a laser de baixa intensidade mostraram resultados favoráveis nos sintomas e reabilitação sensório-motora, mas nenhum considerado clinicamente significativo (Bula-Oyola et al, 2021).…”
Section: Tratamentos Não Farmacológicosunclassified